THE ROLE OF LEADERS IN DETERMINING THE DIRECTION OF SOCIAL GROUPS (A CASE STUDY IN THE MARKETING UNIT OF A COMPANY) - Harsono, Bernardus Danny (PT. Antis International Publisher, 2025)
Objective: This study aims to explore the role of leadership within a social group, specifically in the context of a marketing unit in a company, and how that role influences group direction in alignment with organizational goals. Method: Employing a qualitative research design, data were collected through direct observation and in-depth interviews with selected individuals within the marketing unit to gain insights into leadership dynamics and group behavior. Results: The findings reveal that the leader plays a crucial role in determining the movement and cohesion of the social group, shaping its strategies and behaviors to follow the company’s vision and objectives. Leadership influence was evident in task delegation, motivation, and conflict resolution, which collectively contributed to increased group effectiveness. Novelty: This study contributes to the sociological understanding of leadership not only as a managerial function but as a central element in the formation and direction of social groups in professional environments, particularly within marketing units—a focus that remains underrepresented in existing literature.